Playback survey trial for the Little Owl Athene noctua in the UK. Issue 2 (2nd April 2016) - Clewley, Gary D.; Norfolk, David L.; Leech, Dave I.; Balmer, Dawn E.
ABSTRACT: Capsule: Playback is effective at improving detectability of Little Owls. Aims: To trial a playback survey methodology for Little Owls in the UK to determine detectability and practicalities which could inform potential future national monitoring efforts. Methods: Nocturnal playback surveys were carried out in an open landscape in the east of England in spring 2015. Twelve 2 × 2 km survey squares were each visited four times. Little Owl calls were broadcast from three locations within each square along a linear transect and spaced 500 m apart. The responses of owls of any species were recorded. Little Owl occupancy was later confirmed through existing nest monitoring efforts. Results: Little Owls were detected responding to playback in all survey squares and were confirmed to be breeding in 8 of the 12. Detection and response rates were greater when combining data from multiple broadcast locations. The likelihood of Little Owls responding decreased with greater distance of broadcast location to known nest site, but no relationships were identified with time of evening or the presence of other owl species. Conclusion: Playback methodology proved to be effective at increasing detectability of Little Owls and this study provides an estimated response rate to inform future efforts.